Impact of New Living Environment on Reactive Stress Tolerance in Preadolescent Sports Trainees of Jharkhand - Pahan, Manohar Kumar; Malhan, Vikrant; Nepoleon, Yendrembam (Physical Education Theory and Methodology, 2023)
Study purpose. The purpose of the study was to examine the effect of background experience related to family demography on the selected parameters of reactive stress tolerance in athletes who strictly lived in a training academy for a minimum of two years. Materials and methods. A total of 200 male sports cadets were chosen by the Jharkhand State Sports Promotion Society in Ranchi, with chronological age ranging from 11 to 14 years and 4 years of training. The demographic information (the size of the family, the type of family, the order of birth, the family monthly income, and the location of the home) were considered as independent variables. Stress tolerance parameters (PR correct, PR incorrect, PR omitted, and median reaction time) were chosen as dependent variables. The Shapiro-Wilk test was used to determine data normality, while Levene's test was used to determine homogeneity. The Mann-Whitney U and Kruskal-Wallis tests were used to draw comparisons. For post-hoc comparison, Dunn's test with Holm correction was employed. The threshold for significance was set at p = 0.05. Results. The percentile rank of correct responses (p = 0.005) and median reaction time (p = 0.033) related to birth orders showed significant results. Other factors related to family information and reactive stress tolerance were not significant. Conclusions. According to the findings, it was concluded that being in new environment for a long duration reduced the early living experience related to family demography but effect of birth order still continued.